Dispute Resolution on Unauthorized Liquidation of Futures Positions at the Leading Stock Exchange in India: A Case Study - Brahmaiah, Bezawada (Indian Journal of Finance and Banking, 2020)
The paper studies compliances of Futures Trading rules and regulations of the Stock Exchange .in the derivate market in India. The paper applies case method approach to study the trading practices of trading members of the Exchanges. It investigates the derivative market’s misuses and abuses by the trading members of the Exchange. The paper provides guidance for the appropriate regulatory framework to curtail violations of rules and regulations in Indian derivative market, and enables the investor protection. The results may be generalized in the emerging markets. Hence, researchers are encouraged to study results further in other developed countries. The paper finds that these practices are not only violation of trading rules of the Stock Exchange but also unfair and unethical trading practices. The research findings and results may lack generalizability in a case study approach.